Biodegradable acid based nanocomposite-CuO-ZnO-Ni(OH)2/PA: A novel material for water cleansing. (20th March 2022) - Ahmed, Rabia; Siddiqui, Sharf Ilahi; Al Alwan, Basem; Almesfer, Mohammed; Khanna, Manoj Kumar; Fatima, Bushra; Mishra, Ruby; Ansari, Mohammed Afzal; Oh, Seungdae
Abstract: Rapid industrialization has exposed the human community to serious risks of water toxicity from excessive contamination of fresh water by toxic dyes. Thus, many techniques have been adopted to reduce water contamination. Adsorption technology based on environmentally friendly adsorbents appears to be the best solution; mixed metal-oxide nanocomposites as adsorbents have been in great demand over the past several years. Mixed metal-oxide nanocomposites can be modified using biodegradable materials to meet this demand, although such studies are very rare. This study reports the preparation of phthalic-acid-modified copper–zinc binary oxide coupled with a nickel hydroxide nanocomposite. Copper–zinc binary-oxide-coupled nickel hydroxide nanocomposite was prepared by a simple co-precipitation method and modified with biodegradable phthalic acid. The characterization results revealed the enhanced functional groups and porosity of phthalic-acid-modified nanocomposite, which was used to remove Congo red dye and found to be more suitable than unmodified copper–zinc binary-oxide-coupled nickel hydroxide. Congo red dye removal efficiency of the modified nanocomposite was approximately 30% higher than that with the unmodified nanocomposite under the same conditions. Approximately 2.0 g/L amount of the modified nanocomposite adsorbent could remove about 99% of the 10.0 mg/L concentration of Congo red dye within 120 min at pH = 7.0 and 30 °C. The partition coefficient (∼32.00 mg/g/μM), equilibrium adsorption capacity (∼5.00 mg/g), and maximum adsorption capacity (∼20.0 mg/g) of the modified nanocomposite were also found to be much better than those of the unmodified copper–zinc binary-oxide-coupled nickel hydroxide and other reported adsorbents. The regeneration and reusability test results of the modified nanocomposite for Congo red dye removal suggested that the modified adsorbent was efficient for five cycles. This pioneering study is shown to be efficient for wastewater treatment, and the novelty is based on the use of biodegradable acids. Based on experimental results, it is recommended that more biodegradable acids be used in adsorbent preparation and modification in the future so that sustainable and affordable technologies may be achieved. Graphical abstract: Image 1 Highlights: The novelty of this study is the use of biodegradable acid for the modification of mixed metal oxide. CuO–ZnO–Ni(OH)2 was modified by phthalic acid to remove the toxic dye, Congo red. The modified CuO–ZnO–Ni(OH)2 was found to have high porosity and functional groups. The adsorbent exhibited high Congo red removal efficiency with high sensitivity. The adsorption was reused for five cycles with a slight drop in efficiency.